Phenotypic characterization of soybean genetic resources at multiple locations: breeding implications for enhancing environmental resilience, yield and protein content - Vymyslický, Tomáš; Trněný, Oldřich; Rietman, Hendrik; Balko, Christiane; Đorđević, Vuk; Ranđelović, Predrag; Dybová, Magdaléna (Frontiers in Plant Science, 2025)
IntroductionSoybean is an important legume crop and a leading source of dietary protein and oil in animal feed, as well as an important food for human consumption. The objective of our research was to study soybean genetic resources in context of future protein self-sufficiency both in human and animal nutrition.MethodsCollection of 360 different accessions from various regions worldwide was evaluated across four European locations during two consecutive years in phenotyping trials. The five most important traits of soybean – plant emergence, plant length, protein content, seed yield, and R8 stage – were carefully analysed, revealing significant variability.ResultsTen exceptionally stable genotypes were identified based on their protein content and yield, presenting promising candidates for breeding programs.DiscussionOur findings underscore the importance of integrating genotype-environment interaction analyses into breeding initiatives, considering the observed variability in phenotypic traits across diverse environments and genotypes.